Solving logistics’ problems through an infinite servers queue systems approach - Filipe, J. A.; Ferreira, M. A. M. (International Journal of Business and Systems Research, 2019)
It is exemplified in this article a proceeding based on the busy period concept of infinite servers queues systems to deal with equipment’s failures. Evidently, the occurrence of failures in the equipment is a situation that demands managerial procedures in order to repair the failures as quick as possible and also to minimize the losses in the equipment operation. The model presented here - by means of infinite servers queuing systems - allows to generate system performance measures. It also contributes to solve organizational structures’ problems, by minimizing the risks of the inoperative structures of organizations, which have considerable logistics pernicious consequences for companies and often for regions where they are implanted.